2010
DOI: 10.1194/jlr.m001875
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lipid transfer activity between model nascent HDL particles and plasma lipoproteins: implications for current concepts of nascent HDL maturation and genesis

Abstract: The process of lipidation of apolipoprotein A-I (apoA-I) by the ABCA1 transporter is functionally important in the biogenesis of HDL and in regulating lipid transport and metabolism, which, in turn, is critical for normal human physiology. This process is believed to be one of the major mechanisms by which HDL may protect against atherosclerotic cardiovascular disease ( 1, 2 ). As a result, the molecular mechanisms underlying the origin of plasma HDL have been a subject of intense study.Although it is well est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…It has been shown that apolipoprotein B lipoproteins can be direct acceptors of free cholesterol released from cells in vitro. 16 The importance of preb-1 HDL as a key mediator of ABCA1-mediated cholesterol efflux from macrophages in IR states was recently demonstrated by Attia et al, 17 who measured cholesterol efflux capacity in ABCA1-expressing J774 cells incubated with sera from obese subjects with insulin resistance. They concluded that the preb-1 HDL levels were the major determinants of efflux capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that apolipoprotein B lipoproteins can be direct acceptors of free cholesterol released from cells in vitro. 16 The importance of preb-1 HDL as a key mediator of ABCA1-mediated cholesterol efflux from macrophages in IR states was recently demonstrated by Attia et al, 17 who measured cholesterol efflux capacity in ABCA1-expressing J774 cells incubated with sera from obese subjects with insulin resistance. They concluded that the preb-1 HDL levels were the major determinants of efflux capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Two forms of functionally defi ned PLTP are found in the plasma ( 19 ): an "active" form that can transfer triglyceride-rich phospholipids from VLDLs and chylomicrons to HDL ( 20,21 ), and an "inactive" form that lacks this capability. Between 50 and 90% of total measures, baseline demographic/clinical characteristics, and genetic variants in the PLTP region.…”
mentioning
confidence: 99%
“…It is generally accepted that nascent HDLs acquire unesterified cholesterol and associate with LCAT, leading to cholesterol esterification and their conversion to mature HDL. 34 Our studies provide evidence for another mechanism by which nascent HDLs can enter the mature HDL pool that is enhanced by PLTP-mediated particle remodeling.…”
Section: Discussionmentioning
confidence: 64%